118k views
2 votes
Solve for x. x2−9x+3=0

User Ruthven
by
5.4k points

2 Answers

4 votes

Answer:

x=0.428571

Explanation:

x2−9x+3=0

-7x=3

x=0.428571

User Burak Cakir
by
4.8k points
2 votes

The value of x will be 8.65 or 0.35

Solution:

Given,
x^2-9x+3=0

Here, to solve the given equation, we have to use the quadratic formula,


x=\frac{-b \pm \sqrt{b^(2)-4 a c}}{2 a} \text{ when } a x^(2)+b x+c=0

where a=1; b=-9; c=3 and x is the value to be found.

On substituting the values in the equation we get,


\bold{x=(-(-9)\pm√((-9)^2-4*3*1))/(2*1)} \bold{\rightarrow (9\pm√(81-12))/(2)}}

\bold{\Rightarrow \frac{9\pm\sqrt{69}}{2}}}

The square root of 69 is 8.3

On substituting the value in the above equation we get,


\bold{\Rightarrow (9+8.3)/(2)}} \bold{ \text{ or }} \bold{ (9-8.3)/(2)}}

On solving we get,


\bold{\Rightarrow (17.3)/(2)}} \bold{ \text{ or }} \bold{ (0.7)/(2)}}


\bold {\Rightarrow \therefore \text{ x will be }} \bold{8.65} \bold{\text{ or }} \bold{0.35}

User Silversonic
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.